Pengaruh Efikasi Diri dan Optimisme terhadap Kecemasan pada Mahasiswa Tahun Pertama - Choirun Nisa; Widiawati Widiawati; Azzahra Meita Syamsyiah Putri; Lucky Purwantini (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Anxiety is an emotional reaction characterized by feelings of discomfort, tension, and concern about situations that are considered dangerous, both objectively and subjectively, which are often accompanied by physiological symptoms as well as feelings of helplessness and uncertainty without a clear cause.the subjects in this study were first-year students totaling 134 subjects who represented the population. The sampling technique used in this study was probability sampling with simple random sampling. The data collection method in this study uses psychological scales, namely the anxiety scale, self-efficacy scale, and optimism scale in Likert form. Judging from each X variable, stated self-efficacy predicts anxiety significantly while optimism cannot predict anxiety significantly. Self-efficacy and optimism have a very strong negative relationship with anxiety in first-year students at Islamic University 45 Bekasi..